MULTILITERASI DALAM PENGAJARAN BAHASA INGGRIS: TINJAUAN PUSTAKA SISTEMATIK - Sudirman, Saharun; Ajam, Ali; Pratiwi, Ika (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
A systematic literature review is a systematic research method for collecting, critically evaluating, integrating, and presenting findings from multiple research studies on a research question or topic of interest. This systematic literature review approach aims to investigate the implications of multiliteracy models in English language teaching. This study adopts a framework consisting of population, intervention, comparison, outcome, and context (PICOC), as a report in synthesizing findings from tens articles published in the last tens years, namely from 2014 to 2024. Data was selected from research results using mapping analysis using bibliometric analysis and publish and perish databases taken from Google Scholar and Scopus. The findings of this study can be used as a theoretical framework and reference source to improve teaching and learning in English